(untitled) (Journal of Engineering, 2015)
With the development of computer architecture and its technologies in recent years, applications like e-commerce, e-government, e-governance and e-finance are widely used, and they act as active research areas. In addition, in order to increase the quality and quantity of the ordinary everyday transactions, it is desired to migrate from the paper-based environment to a digital-based computerized environment. Such migration increases efficiency, saves time, eliminates paperwork, increases safety and reduces the cost in an organization. Digital signatures are playing an essential role in many electronic and automatic based systems and facilitate this migration. The digital signatures are used to provide many services and solutions that would not have been possible by the conventional hand-written signature. In the educational environment, the process of issuing the graduation certificates can no longer be restricted to the traditional methods. Hence, a computerized system for issuing certificates of graduation in an electronic form is needed and desired. This paper proposes a Graduation Certificates Issuing System (GCIS) based on digital signature technology. In doing so, this research highlights the state-of-the-art and the art-of-the-practice for some existing digital signature-based systems in the literatures. In addition, eight intertwined elected services are identified, namely: message authentication, entity authentication, integrity, non-repudiation, time stamping, distinguished signing authorities, delegating signing capability and supporting workflow systems. Moreover, this research examines nine existing systems, showing their merits and demerits in terms of these elected services. Furthermore, the research describes the architectural design using the Unified Modeling Language (UML) and provides the concrete implementation of the proposed GCIS. The GCIS is implemented using Visual Basic.Net programming language and SQL Server database management system.